Biophysical investigation of thymoquinone binding to 'N' and 'B' isoforms of human serum albumin: exploring the interaction mechanism and radical scavenging activity1. Issue 24 (15th March 2015) - Ishtikhar, Mohd; Rabbani, Gulam; Khan, Shawez; Khan, Rizwan Hasan
<x xml:space="preserve">Abstract</x> Thymoquinone more strongly interacts with the 'N' isoform in comparison to the 'B' isoform of HSA and also increases its thermal stability but the antioxidant activity is significantly higher at the 'B' isoform of HSA.